Effects of inclusion of proprioception training in the recovery of adults submitted to anterior cruciate ligament reconstruction surgery: a systematic review - Wdson Donizete Da Silva Costa; Flávio Ricardo Guilherme; Stevan Ricardo dos Santos; Eduardo Gauze Alexandrino; Vânia Renata Guilherme; Wilson Rinaldi (Journal of Physical Education (Maringá), 2020)
Anterior cruciate ligament (ACL) rupture is an injury in young adults, triggering undesirable neuromuscular effects. A rehabilitation program is structured with exercises that aid in intensive care training, and proprioceptive training has been proposed as one of the training / rehabilitation methods in patients undergoing ACL reconstruction. Thus, this study aimed to analyze, through a systematic literature review, the effects of including proprioceptive training on different outcomes (stability / balance, proprioception, strength, functional capacity, coordination) after ACL reconstruction surgery in young adults. The search of the articles included studies in the last ten years, being a search conducted in November 2018. Searches were conducted in the electronic databases of PubMed and Science Direct with a following search methodology: (("Proprioception" [Mesh] ) OR "Proprioception" [Word Text]) AND ("Anterior Cruciate Ligament" [Mesh] OR "Anterior Cruciate Ligament Reconstruction" [Mesh] OR "Anterior Cruciate Ligament Injury" [Mesh]). Six studies were selected for the analysis and the results obtained there is insufficient scientific evidence showing the positive effects of training in proprioceptive training after ACL reconstruction in adults, in view of a shortage of studies, such as discrepancies in findings, without time of intervention and in the tests contracted in the analysis of the variables.